Liquid-phase mass transfer in top-blown open-channel flows - R. K. Manna; N. A. Warner (The Institute of Materials, Minerals and Mining, 1991)
Physical modelling of liquid-phase oxygen mass transfer in a water model of part of a proposed new polymetallic smelter has been achieved. A study of solute mass transfer caused by multiple, subsonic air jets contacting superoxygenated water flowing in a channel model of the smelter converting hearth has been carried out. For a wide range of channel flow rates the rate of mass transfer was found to be independent of water velocity. The water model has been used to compare mass transfer for both open-packed and close-packed multiple-lance arrays with circular nozzles of diameters 2.26, 4.95, 10.95 and 24.40 mm. It was found that with fewer of the larger-diameter nozzles a reduction of up to 58% in liquid-phase mass transfer occurred, especially for the close-packed lance configurations. This restriction of liquid-phase mass transfer would result in reduced metal losses in the analogous smelting situation. The larger nozzles, however, exhibited more jet-jet and jet-channel wall interference effects than their smaller counterparts, resulting in an effective reduction in the momentum fluxes of the impinging jets